2002
DOI: 10.1002/1522-2675(200208)85:8<2458::aid-hlca2458>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Synthesis of Aryl-Substituted N-Carbamoyl/N-Thiocarbamoyl Narcotine and Related Compounds

Abstract: The reaction of nornarcotine and 5-bromonornarcotine, synthesized from noscapine, with suitable aromatic isocyanates or isothiocyanates provides a general method for the synthesis of aryl-substituted N-carbamoyl or N-thiocarbamoylnarcotine and related compounds. Similarly, 15a has been prepared via the reduction of the lactone ring moiety of noscapine. Also, an improved procedure, which utilizes narcotine N-oxide ¥ HCl for generation of nornarcotine, is described.Introduction. ± Alkaloids and their analogs are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
40
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 6 publications
1
40
0
Order By: Relevance
“…122 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 Braun reaction, however these were unsuccessful in the synthesis of the secondary amine scaffold. 105,124 It is reported that these conditions resulted in cleavage of 6 at the benzylic and tertiary centers adjacent to the amine functionality. 105 Non-classical Polonovski reaction conditions 125 successfully delivered the desired secondary amine core for further functionalization.…”
Section: '-Halonoscapine Analogsmentioning
confidence: 99%
See 3 more Smart Citations
“…122 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 Braun reaction, however these were unsuccessful in the synthesis of the secondary amine scaffold. 105,124 It is reported that these conditions resulted in cleavage of 6 at the benzylic and tertiary centers adjacent to the amine functionality. 105 Non-classical Polonovski reaction conditions 125 successfully delivered the desired secondary amine core for further functionalization.…”
Section: '-Halonoscapine Analogsmentioning
confidence: 99%
“…105 Non-classical Polonovski reaction conditions 125 successfully delivered the desired secondary amine core for further functionalization. 105 The reaction procedure began with the synthesis of the tertiary amine oxide using m-CPBA in chloroform followed by the acidification of tertiary amine oxide with hydrochloric acid to form the tertiary amine oxide as the hydrochloride salt. 126 Noscapine-N-oxide hydrochloride was then dissolved in a citric acid buffer solution containing Fe (III) -citrate which gave 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 the desired secondary amine core for further derivatisation.…”
Section: '-Halonoscapine Analogsmentioning
confidence: 99%
See 2 more Smart Citations
“…indeed, our initial efforts have been quite encouraging in that we have some more effective derivatives of the lead compound noscapine. [6][7][8][9] this led us to build a reasonable quantitative structure activity relationship (qsaR) model. the qsaR model guided us in rationally designing the azido derivatives of noscapine with superior activity.…”
mentioning
confidence: 99%